Brief Online Interventions to Improve 5K Running - Daniel T Robinson; Stuart W Holliday; Ross Cloak; Andrew M Lane (Journal of Coaching and Sports Science, 2023)
Athletes and coaches strive to identify and learn to use interventions to enhance performance. The goal to be a competent user of psychological skills which aid performance is common among coaches and athletes. However, how frequently such skills are used and how they are learned is less well understood. Many athletes experience plateaus in performance despite efforts to improve, and as such are prime candidates to test interventions to enhance performance. To he present study investigate the effectiveness of learning brief psychological skills among athletes who competed in a weekly 5km time trial whose performances had plateaued. Participants (n = 7) volunteered to follow brief psychological skills training which involved watching brief videos on how to use one of self-talk, reappraisal, if-then plans, or a non-treatment condition, but in the context of the study represent receiving encouragement to mentally prepare. Data analysis compared intervention results with baseline data taken from 2 months of data before the intervention. Results Psychological skills usage associated with finishing 347.37m (p = .019) ahead of baseline. Post-race reflections indicated using psychological skills helped re-appraise fatigue. Findings offer encouraging data on encouraging runners to engage in mental preparation and that following brief psychological skills training is helpful, however, confirmatory research is needed with larger samples.